(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The staff is the very foundation on which the success of the company is based. Personnel management implies the skillful management of the activities of employees, ensuring the development and profitability of the enterprise. Management can be considered skillful and competent in the case when each employee of the company applies his abilities and skills for the best performance of his duties, is interested in the high results of his work and retains the desire to work in this particular company.